2017
DOI: 10.2196/jmir.7581
|View full text |Cite
|
Sign up to set email alerts
|

Public Awareness and Use of German Physician Ratings Websites: Cross-Sectional Survey of Four North German Cities

Abstract: BackgroundPhysician rating websites (PRWs) allow patients to rate, comment, and discuss physicians’ quality. The ability of PRWs to influence patient decision making and health care quality is dependent, in part, on sufficient awareness and usage of PRWs. However, previous studies have found relatively low levels of awareness and usage of PRWs, which has raised concerns about the representativeness and validity of information on PRWs.ObjectiveThe objectives of this study were to examine (1) participants’ aware… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 33 publications
2
28
0
1
Order By: Relevance
“…But there could also be a sampling effect, as the aforementioned studies were all conducted using online panel sampling. However, a recent study in Germany that used a cross-sectional random sample survey found awareness at 72.5% [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…But there could also be a sampling effect, as the aforementioned studies were all conducted using online panel sampling. However, a recent study in Germany that used a cross-sectional random sample survey found awareness at 72.5% [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Terlutter et al [ 32 ] discovered in Germany (in 2012) that 26% of the population had used a doctor-rating website before, although it was not clear for which purpose. More recently, in 2017, researchers found usage of doctor-rating websites in Germany at 43.6% [ 21 ] In Austria, researchers conducted an experimental study based on a convenient sample and found that 47% of respondents had used a doctor-rating website, and 6% had used it to leave feedback [ 46 ]. The difference in results may be due to regional differences in the diffusion of doctor-rating websites and the adoption of the internet for seeking health information.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with the growing adoption of social media and online review platforms in various sectors, patients in different countries such as United States [25,27], Germany [11,32], and China [21] use physician rating websites (PRWs) to review physicians and write comments about them. The reviews shared in this way can help other patients make more informed and judicious decisions on which doctors to visit.…”
Section: Introductionmentioning
confidence: 99%